2018
DOI: 10.1002/eat.22885
|View full text |Cite
|
Sign up to set email alerts
|

Associations between healthcare use and disordered eating among female veterans

Abstract: These findings confirm the high probability that female veterans with EDs are utilizing significant VA mental health resources. Screening for EDs may be particularly important in VA medical and mental health settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Not only was health service utilization in these areas greater among women with higher eating disorder symptoms, but even moderately elevated eating disorder symptom scores (i.e., +1 standard deviation above the sample mean on the EDE-Q) showed increases of 17%-58% in the number of overall primary care, mental health, and telephone visits. These findings on objective health service utilization are consistent with prior work which has shown higher self-reported health service utilization among veterans with eating disorder symptoms (Huston et al, 2018;Mitchell et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Not only was health service utilization in these areas greater among women with higher eating disorder symptoms, but even moderately elevated eating disorder symptom scores (i.e., +1 standard deviation above the sample mean on the EDE-Q) showed increases of 17%-58% in the number of overall primary care, mental health, and telephone visits. These findings on objective health service utilization are consistent with prior work which has shown higher self-reported health service utilization among veterans with eating disorder symptoms (Huston et al, 2018;Mitchell et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…The present study builds upon existing research (Huston et al, 2018;Striegel-Moore et al, 2008) by describing chart-verified health service utilization in a sample of United States military veterans enrolled in the Veterans Health Administration. Our primary aim was to describe outpatient treatment engagement in women veterans who report eating disorder symptoms through an analysis of health service utilization over the course of 5 years.…”
Section: Present Studymentioning
confidence: 99%
“…In female veterans, estimates of probable EDs range from 7.5% to 70% depending on population and sample size with those experiencing mental health difficulties having higher estimates (Arditte Hall et al, 2018; Blais et al, 2019; Breland, Donalson, Dinh, et al, 2018; Breland, Donalson, Li, et al, 2018; Buchholz et al, 2018; Huston et al, 2018, 2019). Huston et al (2019) identified that 0% of the female veteran sample met diagnosable criteria for probable AN, 7.83% for probable BN, and 6.28% for probable BED, with 14.11% meeting the criteria for any ED.…”
Section: Resultsmentioning
confidence: 99%
“…EDs and DE in servicemembers negatively impact individuals and the military. Female veterans with EDs used VA mental healthcare more often and all genders had a higher risk for other mental health conditions (Huston et al, 2018; Rosenbaum et al, 2016). Although infertility was not related to an ED diagnosis in female veterans, ED behaviors did have a negative relationship with relationship satisfaction (Blais et al, 2019; Mancuso et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation